Systematic review with meta‐analysis: faecal diversion for management of perianal Crohn's disease. Issue 7 (11th August 2015) - Singh, S.; Ding, N. S.; Mathis, K. L.; Dulai, P. S.; Farrell, A. M.; Pemberton, J. H.; Hart, A. L.; Sandborn, W. J.; Loftus, E. V.
Summary Background Temporary faecal diversion is sometimes used for management of refractory perianal Crohn's disease (CD) with variable success. Aims To perform a systematic review with meta‐analysis to evaluate the effectiveness, long‐term outcomes and factors associated with success of temporary faecal diversion for perianal CD. Methods Through a systematic literature review through 15 July 2015, we identified 16 cohort studies (556 patients) reporting outcomes after temporary faecal diversion. We estimated pooled rates [with 95% confidence interval (CI)] of early clinical response, attempted and successful restoration of bowel continuity after temporary faecal diversion (without symptomatic relapse), and rates of re‐diversion (in patients with attempted restoration) and proctectomy (with or without colectomy and end‐ileostomy). We identified factors associated with successful restoration of bowel continuity. Results On meta‐analysis, 63.8% (95% CI: 54.1–72.5) of patients had early clinical response after faecal diversion for refractory perianal CD. Restoration of bowel continuity was attempted in 34.5% (95% CI: 27.0–42.8) of patients, and was successful in only 16.6% (95% CI: 11.8–22.9). Of those in whom restoration was attempted, 26.5% (95% CI: 14.1–44.2) required re‐diversion because of severe relapse. Overall, 41.6% (95% CI: 32.6–51.2) of patients required proctectomy after failure of temporary faecal diversion. There was no difference in the successful restoration of bowel continuity after temporary faecal diversion in the pre‐biological or biological era (13.7% vs. 17.6%, P = 0.60), in part due to selection bias. Absence of rectal involvement was the most consistent factor associated with restoration of bowel continuity. Conclusions Temporary faecal diversion may improve symptoms in approximately two‐thirds of patients with refractory perianal Crohn's disease, but bowel restoration is successful in only 17% of patients.